Zuid Midden Timor under the Dutch Control 1905-1942 - Sarlota Naema Sipa; A. M. Djuliati Suroyo; Endang Susilowati (Indonesian Historical Studies, 2017)
This study is aimed at retracing the Dutch colonial government  in South Middle Timor or Zuid Midden Timor in the beginning of 20th century. Intending to expand its controlled territories, to exploit the sandalwood trade and introduce Christianity, the colonial government then domiclied in Kupang entered the inland parts of Timor island, to be prescisely in Molo in 1905. The Ducth colonial government defeated the local meos (soldiers), the Molo meo, Amabuan meo and the Amanatun meo. These three regions were later formed as a governmental administration zone by the East Indies, equivalent to  a landschaap and were later combined in an onderafdelling-level administration unit called Zuid Midden Timor, with Molo as its capital city. As the capital city, Molo housed all public administration affairs, markets and shops, which were all centered in Molo. Until the end of the Dutch control in 1942, the Dutch colonial government had left its influences in culture, education, social aspects and governmental politics.